2018
DOI: 10.1080/14767058.2017.1421935
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric reference curves for term neonates born at 3400 meters above sea level

Abstract: Reference curves were developed for the 3rd, 10th, 50th, 90th, and 97th percentile for weight, height, head circumference (HC), ponderal index (PI), and HCBWI for term newborns according to sex born at 3400 m above sea level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
0
1
1
Order By: Relevance
“…Therefore, risk factors that may lead to abnormal fetal growth, including maternal comorbidities during pregnancy, should be excluded when establishing a birth growth curve ( 7 ). Villamonte-Calanche et al ( 22 , 23 ) found a neonatal growth curve at 3,400 m in Peru, similar to that of the international standard, unlike our results. However, their study ignored factors, including residence altitude or pregnancy comorbidities.…”
Section: Discussioncontrasting
confidence: 89%
“…Therefore, risk factors that may lead to abnormal fetal growth, including maternal comorbidities during pregnancy, should be excluded when establishing a birth growth curve ( 7 ). Villamonte-Calanche et al ( 22 , 23 ) found a neonatal growth curve at 3,400 m in Peru, similar to that of the international standard, unlike our results. However, their study ignored factors, including residence altitude or pregnancy comorbidities.…”
Section: Discussioncontrasting
confidence: 89%
“…12 Existen pocos países que presenten un gradiente altitudinal como los ubicados sobre la cordillera de los Andes. Los antecedentes más abundantes que analizan la variación del PN en relación con la altura corresponden a Perú y a Bolivia; [13][14][15][16][17][18] los trabajos que analizan el tamaño al nacer en estos ambientes extremos son escasos.…”
Section: Introductionunclassified